Three dimensional sonography and 3D power doppler angiography with Levovist in differentiating adnexal tumors in postmenopausal women - Czekierdowski, Artur; Kotarski, Jan (Menopause Review/Przegląd Menopauzalny, 2002)
Neoangiogenesis in the uterus and adnexa may be a hallmark of malignant tumor growth in postmenopausal women. Doppler ultrasound blood flow measurements have been used extensively over past two decades in order to detect ovarian tumor vascularity and risk of malignancy assessment. The objective of this paper is to present initial results of postmenopausal adnexal tumors assessment with the use of 3D ultrasonography and 3D power Doppler sonoangiography. Additionally, preliminary observations of 3D ultrasound characterization of adnexal tumors with the use of contrast media (Levovist) are presented. Thirty-four postmenopausal women with adnexal tumors were examined preoperatively. Following morphological (papillae, septae, tumor size and volume) and color Doppler (PI, RI, Vmax and TAMX) assessment 3D ultrasound of adnexal tumors was performed. Various scanners were used and included the use of Siemens Elegra, ATL 5000 HDI and Voluson V530 and V730 machines. Following variables were studied: inner wall structure, presence of papillae, thickening >3 mm of septa as well as vascular branching pattern, number and localization of small blood vessels and the presence of vascular anastomoses. Power Doppler combined with 3D sonography predicted malignancy with a sensitivity of 93,7% (15 of 16 patients). This compares favourably with commonly used morphological and Doppler criteria which had sensitivity in range of 45% to 87,5%. We conclude that selective use of 3D sonography and power Doppler angiography could be used to better characterize adnexal tumors. This would allow to stratify affected postmenopausal patients into individuals who may not be operated, may have less invasive procedure and these with truly increased risk for ovarian malignancy who should be referred to the gynecologic oncologist.